2019
DOI: 10.1186/s12944-019-1047-y
|View full text |Cite
|
Sign up to set email alerts
|

Minimal effective dose of lactic-fermented egg white on visceral fat in Japanese men: a double-blind parallel-armed pilot study

Abstract: Background We previously reported that the consumption of 8 g of protein per day in the form of lactic-fermented egg white (LAFEW) improves visceral fat obesity. In this study, we investigated the minimum effective intake of LAFEW for visceral fat reduction in the Japanese males with mild obesity. Methods Twenty-two Japanese adult males with a Body mass index (BMI) ≥24 and a waist circumference ≥ 85 cm were included in this study. The subjects were divided into three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…If they were not, the FLE group would have received a lower amount of dietary protein and shown a weaker effect of visceral fat reduction. In a previous study, we evaluated the lowest effective dose of egg white protein in humans, and have reported that 8 g of egg white protein reduced more visceral fat than 6 g of egg white [24].…”
Section: Discussionmentioning
confidence: 99%
“…If they were not, the FLE group would have received a lower amount of dietary protein and shown a weaker effect of visceral fat reduction. In a previous study, we evaluated the lowest effective dose of egg white protein in humans, and have reported that 8 g of egg white protein reduced more visceral fat than 6 g of egg white [24].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to intake of soy protein or carbohydrates, a similar dose of whey proteins reduced waist circumference, 8 suggesting an effect on the sWAT because of the stronger correlation between waist circumference and the sWAT than vWAT 102,103 (Table 1). Switching the protein quality to one of the nine individual proteins that constitute whey, notably lactoferrin (Lf), 101 and using the enteric‐coated form of the protein (E‐Lf) to protect it from digestion in the upper digestive tract, also switched the effect, which reduced vWAT, 9 similar to intake of fermented egg white, 13 whereas intake of soy proteins reduced only the sWAT 12 (Table 1). The specificity of soy proteins to affect one depot was not seen using the peptide β‐conglycin, derived from soy protein 11 .…”
Section: Introductionmentioning
confidence: 99%